Insights into the microbiota of raw milk from seven breeds animals distributing in Xinjiang China - Luo, Baolong; Dong, Fujin; Liu, Yuyang; Du, Jie; Sun, Hailong; Ni, Yongqing; Zhang, Yan (Frontiers in Microbiology, 2024)
Owing to its high nutritional content, raw milk contains a rich microbiota. Thus, to study microorganisms present in raw milk available in Xinjiang China, 142 raw milk samples from seven animal breeds (cow, sheep, goat, donkey, horse, camel, and yak) and four regions (Hami, Tarbagatay, Kashgar, and Ili) were analyzed by high-throughput DNA sequencing. These microorganisms were characterized by 10 dominant phyla. Proteobacteria (68.33%) was the major phylum, followed by Firmicutes (18.80%) and Thermi (3.16%). Horse milk contained more Bacteroidetes, sheep milk contained more Gammaproteobacteria, and donkey milk contained more unclassified sequences. Camel and donkey milk contained the highest and lowest bacterial diversity compared with that contained by the remaining milk samples, respectively. Additionally, spoilage microorganisms, including Chryseobacterium, Propionibacterium, and Flavobacterium, and pathogenic bacteria, including Ochrobactrum anthropi and Sphingomonas, were more prevalent in horse and yak milk, whereas probiotic lactic acid bacteria (LAB), such as Leuconostoc, Lactococcus, or Lactobacillus, were more prevalent in goat, donkey, and camel milk. Furthermore, Moraxella was abundantly present in goat, camel, and yak milk, Acinetobacter was more abundant in camel milk, and Pseudomonas was relatively abundant in sheep and donkey milk. Overall, specific harmful microorganisms and probiotic lactic acid bacteria were found in the raw milk samples obtained from different animals, which provided a basis for preventing and controlling the growth of harmful bacteria, as well as investigating probiotic resources in raw milk.